Sandwich Structured Composites for Aeronautics: Methods of Manufacturing Affecting Some Mechanical Properties - Aneta Krzyżak; Michał Mazur; Mateusz Gajewski; Kazimierz Drozd; Andrzej Komorek; Paweł Przybyłek (International Journal of Aerospace Engineering)
Sandwich panels are composites which consist of two thin laminate outer skins and lightweight (e.g., honeycomb) thick core structure. Owing to the core structure, such composites are distinguished by stiffness. Despite the thickness of the core, sandwich composites are light and have a relatively high flexural strength. These composites have a spatial structure, which affects good thermal insulator properties. Sandwich panels are used in aeronautics, road vehicles, ships, and civil engineering. The mechanical properties of these composites are directly dependent on the properties of sandwich components and method of manufacturing. The paper presents some aspects of technology and its influence on mechanical properties of sandwich structure polymer composites. The sandwiches described in the paper were made by three different methods: hand lay-up, press method, and autoclave use. The samples of sandwiches were tested for failure caused by impact load. Sandwiches prepared in the same way were used for structural analysis of adhesive layer between panels and core. The results of research showed that the method of manufacturing, more precisely the pressure while forming sandwich panels, influences some mechanical properties of sandwich structured polymer composites such as flexural strength, impact strength, and compressive strength.